Financial Ratios and Stock Prices in Food Beverage Firms: Rasio Keuangan dan Harga Saham di Perusahaan Makanan dan Minuman - Nadiyatus Setia Ningrum; Heri Widodo (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Stock prices are widely used as indicators of firm value in capital markets and reflect investor assessments of corporate financial performance. Specific Background In Indonesia, food and beverage companies represent a growing manufacturing sector that attracts investors due to stable demand and continuous expansion. Knowledge Gap Previous studies report inconsistent findings regarding the role of earnings per share, debt structure, and equity returns in explaining stock price movements, particularly across different periods and sectors. Aims This study aims to examine the relationship between Earning Per Share, Debt to Equity Ratio, and Return on Equity on stock prices of food and beverage companies listed on the Indonesia Stock Exchange during 2019–2023. Results Using multiple linear regression on secondary data from selected firms, the findings indicate that Earning Per Share shows a significant positive relationship with stock prices, while Debt to Equity Ratio also demonstrates a significant association. Return on Equity displays a positive but not consistently significant relationship. Novelty The study provides updated empirical evidence by focusing on a specific industrial sector and a recent observation period. Implications The results highlight the importance of profitability and capital structure indicators as key considerations for investors and corporate management in evaluating stock price dynamics. Keywords: Earning Per Share,Debt to Equity Ratio,Return on Equity,Stock Price,Indonesia Stock Exchange Key Findings Highlights: Profit per share demonstrates a strong statistical relationship with market valuation. Leverage structure is closely associated with investor assessment in the observed sector. Equity return shows varying relevance across firms and periods.